Current Advances of Nanocarrier Technology-Based Active Cosmetic Ingredients for Beauty Applications - Zhou H; Luo D; Chen D; Tan X; Bai X; Liu Z; Yang X; Liu W (Dove Medical Press, 2021)
Hong Zhou,1 Dan Luo,2 Dan Chen,2 Xi Tan,1 Xichen Bai,1 Zhi Liu,1 Xiangliang Yang,1,2 Wei Liu1,2 1College of Life Science and Technology, Huazhong University of Science and Technology, Wuhan, 430074, Hubei, People's Republic of China; 2National Engineering Research Center for Nanomedicine, Huazhong University of Science and Technology, Wuhan, 430075, Hubei, People's Republic of ChinaCorrespondence: Wei LiuCollege of Life Science and Technology, Huazhong University of Science and Technology, 1037 Luoyu Road, Wuhan, 430075, Hubei, People's Republic of ChinaTel/Fax +86 27 8779 2147Email wliu@hust.edu.cnAbstract: Nanocarrier technology has been effectively applied to the development of drug delivery systems to overcome the limitations of traditional preparation. Its application has been extended to various pharmaceutical fields from injection preparation to oral preparation and external preparation, and now it has appeared in the field of cosmetics for beauty applications. The widespread influence of nanocarrier in the cosmetics industry is due to the fact that nanocarrier can effectively promote the percutaneous penetration and significantly increase skin retention of active components in functional cosmetics. Meanwhile, nanocarrier can effectively improve the water dispersion of insoluble active cosmetic ingredients, enhance the stability of efficacy components and achieve the codelivery of diverse cosmetics active ingredients. In this review, we summarized the current progress of nanocarrier technology in the functional cosmetics, including the types and the routes of dermal/transdermal drug delivery nanocarriers used in the functional cosmetics, the mechanism of nanocarriers promoting the percutaneous penetration of active cosmetic ingredients, the application and efficacy evaluation of different active cosmetic ingredients in nanocarriers and discussing the potential risks to human. This will provide a useful reference for the further development of nanocarriers in the field of functional cosmetics.Keywords: nanocarrier technology, functional cosmetics, active cosmetic ingredients, skin penetration and positioning, efficacy evaluation, codelivery nanocarriers